20 Linking pediatric primary care and systems: DULCE expansion via quality improvement advances patient-centered care and addresses health-related social needs. (25th November 2019) - Arbour, MaryCatherine; Floyd, Baraka; Morton, Samantha; Atwood, Sidney; Doyle, Stephanie; Hampton, Patsy; Sege, Robert
Abstract : Background: American Academy of Pediatrics Bright Futures™ 4th edition health supervision guidelines prioritize screening for and addressing health-related social needs (HRSN) in the patient centered medical home. Time constraints, lack of knowledge of resources, and other priorities make implementing these recommendations challenging. DULCE (Developmental Understanding and Legal Collaboration for Everyone) is an evidence-based intervention that embeds a community health worker in an interdisciplinary team that includes a pediatrician, mental health clinician, legal partner, and early childhood system representative to screen for and address HRSN, maternal depression, intimate partner violence, and to build on family strengths. Objectives: To adapt DULCE at five sites across the U.S., so that by July 31, 2018, 75% of families receive all routine healthcare (RHC) visits on time, 95% are screened for seven HRSN, and 90% of families with concrete supports needs and 75% of families with maternal depression or intimate partner violence needs receive support. Methods: We used a 19-month technical assistance approach with QI coaching. Results: The percent of families that completed all RHC visits on time increased from 46% to 65%. More than 94% of families were screened for HRSNs, 70% had one or more positive screen, and 88% of those were provided resources. Most prevalent needs were for financial assistance (53%), food (46%), depression support (14%) and housing stabilization (13%). Conclusions: QI-supported DULCE expansion increased by 50% the proportion of children receiving all RHC visits and strengthened the healthcare system's capacity to proactively address families' needs via integration of existing resources.